(untitled) (Scientific journal of the Fergana State University, 2023)
The article reflects on the cognitive analysis of the concept of "Man", which is considered a carrier of language and one of the complex concepts. Uzbek linguistics mentions that human categories are not fully characterized and their cognitive semantics are not analyzed.